Diagnosis of Platelet Function Disorders: A Challenge for Laboratories - Wagner, Miriam; Uzun, Günalp; Bakchoul, Tamam; Althaus, Karina (Hämostaseologie, 2022)
In patients with normal plasmatic coagulation and bleeding tendency, platelet function defect can be assumed. Congenital platelet function defects are rare. Much more commonly they are acquired. The clinical bleeding tendency of platelet function defects is heterogeneous, which makes diagnostic approaches difficult. During the years, a large variety of tests for morphological phenotyping and functional analysis have been developed. The diagnosis of platelet function defects is based on standardized bleeding assessment tools followed by a profound morphological evaluation of the platelets. Platelet function assays like light transmission aggregation, luminoaggregometry, and impedance aggregometry followed by flow cytometry are commonly used to establish the diagnosis in these patients. Nevertheless, despite great efforts, standardization of these tests is poor and in most cases, quality control is lacking. In addition, these tests are still limited to specialized laboratories. This review summarizes the approaches to morphologic phenotyping and platelet testing in patients with suspected platelet dysfunction, beginning with a standardized bleeding score and ending with flow cytometry testing. The diagnosis of a functional defect requires a good collaboration between the laboratory and the clinician.
Keywords: platelet function defect; light transmission aggregometry; inherited platelet disorder; granule defect